Kondisi Sosial Ekonomi Rumahtangga Pekebun Kopi Arabika (Coffea Arabica Linn) Di Desa Langda Kecamatan Buntu Batu Kabupaten Enrekang - Sudarman, Sudarman (UNIVERSITAS NEGERI MAKASSAR, 2017)
This study aims to examine the socio-economic conditions of household Arabica Coffee planters in Langda Village. The analysis technique used in this study is descriptive analysis. Sampling was done randomly with a total sample of 40 people from 161 populations. The results showed that (1) Arabica Coffee Planters in Langda Village were mostly classified as elderly (45-65) years, ie 23 or 58%, besides in terms of education level, Arabica Coffee planters in Langda Village were included in the lower category Elementary School and No Elementary School with a total percentage of 52.00%. (2) 50% of Arabica Coffee Planters have 3 - 4 Household members and 75% of Arabica Coffee Planters have dependents 1 - 4 people (small category). (3) The average household income of Arabica Coffee growers in a year is Rp.17,016,000 derived from Arabica Coffee business income and income outside the Arabica Coffee business with a comparison of the average income of Rp.5,867,000 and Rp.11,149. 000. (4) There are 85% of households that can meet their minimum basic needs, while 15% of households fulfilling their minimum basic needs are not met.